Operational research. - HARPER,W.M.; LIM,H.C. (London pitman publishing, 1982)
Covers all aspects of operational research including optimization methods, decision theory, stochastic models, simulation, game theory, queueing systems, inventory and reliability, among others.
this book is written for business students who, having only elementary mathematical knowledge, need to understand the concepts and techniques of mathematical analysis.
index
E.M.I
Keywords: Operations research; Operations research; Economics